Spring-Mass Behaviour during the Run of an International Triathlon Competition - Le Meur, Y.; Thierry, B.; Rabita, G.; Dorel, S.; Honnorat, G.; Brisswalter, J.; Hausswirth, C. (International Journal of Sports Medicine, 2013)
We investigated the changes in step temporal parameters and spring-mass behaviour during the running phase of a major international triathlon competition. 73 elite triathletes were followed during the 2011 World Championships Grand Final. The running speed, ground contact and flight times were assessed over a 30 m flat section at the beginning of the 4 running laps and towards the finish line, by using a high-frequency camera (300 Hz). The leg and vertical stiffness, and vertical displacement of the mass centre were calculated from step temporal characteristics. A concomitant decrease in running speed, vertical stiffness and leg stiffness was reported during the 4 running laps, except towards the finish line, where these parameters increased. Running biomechanics was not affected between the beginning and the end of the 10 km run, when triathletes were compared for the same running speed (1.68±0.16 m vs. 1.70±0.17 m for step length, 3.18±0.11 Hz vs. 3.16±0.15 Hz for step rate, 12.87±3.14 kN.m − 1 vs.12.76±3.05 kN.m − 1 for Kleg, 31.18±4.71 kN.m − 1 vs.30.74±3.88 kN.m − 1 for Kvert, at lap1 and finish, respectively). Multiple regression models revealed that both step rate change and step length change were correlated with running speed change and that the standardized partial regression coefficient was higher for step length change than for step rate. Independent of the cofounding effect of speed and despite the neuromuscular fatigue previously shown after long-duration events, the lower limb mechanical stiffness and the overall spring-mass regulation were not altered over the 10 km triathlon run in elite competitors. This study showed also that step length explained, to a greater extent than step frequency, the running speed variance in elite triathletes.
Keywords: biomechanics; elite triathletes; running pattern; stiffness